Profile of Bioactive Components and Antioxidant Activity of Aronia melanocarpa Fruits at Various Stages of Their Growth, Using Chemometric Methods - Natalia Dobros; Agnieszka Zielińska; Paweł Siudem; Katarzyna Dorota Zawada; Katarzyna Paradowska (MDPI AG, 2024)
Aronia (chokeberry, Aronia melanocarpa) is a valuable fruit that combines the health benefits of green tea and red wine and is gaining popularity worldwide. Aronia has a unique chemical composition with strong antioxidant properties, including anthocyanins and chlorogenic acids (CGAs). However, it remains unclear which specific compounds or groups are primarily responsible for the antioxidant properties of chokeberry. Therefore, an analysis of the antioxidant properties of aronia berries based on geographical region and their variability during ripening (from green to frostbitten fruit) was conducted. The fruits were collected from three locations for two years. The aim of our work was to identify the compounds responsible for the antioxidant properties of aronia berry extracts by using chemometric methods. The analyses of anthocyanins and CGAs were performed using HPLC-DAD, and the antioxidant capacity was assessed by FRAP and DPPH methods. The PCA analysis also considered variations in temperature and precipitation. The chemometric analysis revealed a strong correlation between radical-scavenging properties and the content levels of chlorogenic acids. The results obtained in this study show that unripe green chokeberry fruits exhibit the highest antioxidant properties, which can be attributed to the high content of CGAs at this stage.